2012
DOI: 10.2147/sar.s26288
|View full text |Cite
|
Sign up to set email alerts
|

Comparing methadone and buprenorphine maintenance with methadone-assisted withdrawal for the treatment of opioid dependence during pregnancy: maternal and neonatal outcomes

Abstract: Pregnancy can motivate opioid-dependent women to seek substance abuse treatment. Research has demonstrated that although prenatal exposure to buprenorphine results in less severe neonatal abstinence syndrome (NAS) relative to prenatal methadone exposure, the maternal and other neonatal outcomes are similar for the two medications. Maternal and neonatal outcomes for opioid-dependent pregnant women receiving these medications have not been systematically ompared with methadone-assisted withdrawal. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The subsequent return to use of illicit opioids subjects pregnant women and the fetus to all the risks associated with such psychoactive substance use (eg, Kaltenbach et al, 1998 ; Mattick et al, 2009 ). Despite this concern regarding opioid use relapse, a secondary data analysis reported that a few studies support the concept that a small minority of women (16%) are successful at completing medication-assisted withdrawal and remaining in drug-free treatment until delivery (eg, Lund et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent return to use of illicit opioids subjects pregnant women and the fetus to all the risks associated with such psychoactive substance use (eg, Kaltenbach et al, 1998 ; Mattick et al, 2009 ). Despite this concern regarding opioid use relapse, a secondary data analysis reported that a few studies support the concept that a small minority of women (16%) are successful at completing medication-assisted withdrawal and remaining in drug-free treatment until delivery (eg, Lund et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, with exposure throughout pregnancy to opioid maintenance medications, there is a 60-80% incidence of neonatal abstinence syndrome, (4) often requiring a stay in the Neonatal Intensive Care Unit. It is unclear, however if maintenance medications, as opposed to medication-assisted withdrawal, should be the standard of care for pregnant women with prescription opioid use disorder (5) and if so, how best to taper these medications.…”
Section: Assessment Of Pertinent and Challenging Clinical Issuesmentioning
confidence: 99%
“…(10) Further, newborn outcomes including neonatal abstinence syndrome appear to be improved among women undergoing medication-assisted withdrawal. (5,10,39-41) At present, however it remains unclear if pregnant women with a prescription opioid use disorder that undergo medication-assisted withdrawal are at high risk for relapse to prescription opioid use or other drug use.…”
Section: Diagnosis and Treatment Of An Opioid Use Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have mainly reported findings from relatively short in-patient periods of withdrawal/tapering for heroin-dependent pregnant women [11,12,14,26]. Gradual tapers over a longer period of time for pregnant women stabilized on methadone or buprenorphine is the preferred method described in the United States and Norwegian treatment guidelines [8,27], if a woman chose to taper during pregnancy [28].…”
Section: Introductionmentioning
confidence: 99%